Bands of Fontana are caused exclusively by the sinusoidal path of axons in peripheral nerves and predict axon path; evidence from rodent nerves and physical models. Issue 2 (13th November 2018) - Alvey, Luke M.; Jones, James F. X.; Tobin‐O'Brien, Cathal; Pickering, Mark
Abstract: The precise cause of the bands of Fontana, striations on peripheral nerves visible to the naked eye, has been the subject of debate for hundreds of years. Some researchers have described them as reflecting the sinuous course of nerve fibres passing through nerves, and others have proposed that endoneurial collagen and sheaths surrounding nerves play a role in their appearance. We hypothesised that the bands are caused exclusively by reflection of light from the surfaces of nerve fibres travelling in phase in sinusoidal waveforms through peripheral nerves. We aligned images of obliquely illuminated nerves with confocal images of axons in those nerves, and the numbers and positions of the bands precisely matched the axonal waves. We also developed three‐dimensional models of nerves with representations of the sinusoidal path of axons at their surface. We observed patterns resembling the bands of Fontana when these models were obliquely illuminated. This provides evidence that the bands of Fontana can be caused by light reflected sinusoidal path of axons alone. We subsequently describe a mechanism of band production based on our observations of both nerves and models. We report that smaller diameter nerves such as phrenic nerves and distal branches of sciatic nerves have shorter band intervals than larger nerves, such as proximal trunks of sciatic nerves, and that shorter band intervals correlate with longer axons per unit length of nerve, which suggests a greater tolerance to stretch. Inspection of banding patterns on peripheral nerves may permit prediction of axon length within nerves, and assist in the interpretation of nerve conduction data, especially in diseases where axon path has become altered.